Influencia de las tecnologías de la información y la comunicación (Tics) en el desarrollo profesional de las secretarias en las instituciones públicas del cantón la Libertad, provincia de Santa Elena, año 2015 - Quimí Delgado, Mercy Edith (2015)
This research work is based on known technology influence the professional development of the secretariats in the public institutions of the La Libertad Canton, province of Santa Elena. It became known that the use of technology it is very important in the daily work since it gives agility, quality and efficiency to the work that they perform. In conclusion considering this aspect, it is determined that you must give importance to the technology in the field of education, highlighting their real possibilities to generate knowledge, the advantages and disadvantages that offers training in values of citizens, and on that dimension, provoking significant changes in the mentality of them to apply them in their daily lives. Determined the influence of technology in the professional development of the secretariats and proposed a guide to training of technological resources, secretarial area of the public institutions of the La Libertad Canton, province of Santa Elena, which applied the methods of inductive - deductive, analytic - synthetic, in order to analyze the results obtained in the research and to draw conclusions and appropriate recommendations. Keywords: Influence of Techniques of information and communication technology, secretaries.